Closet smarts : find flattering fashions that don't cost a fortune, revamp your closet–what to keep, what to toss, what to wear with what, clothes you should never wear–and why, fill wardrobe gaps, the truth about color, clothes, and you /: find flattering fashions that don't cost a fortune, revamp your closet–what to keep, what to toss, what to wear with what, clothes you should never wear–and why, fill wardrobe gaps, the truth about color, clothes, and you. (2006) - Unknown
No abstract available